Enhancing Students’ Understanding of Fiqh through the Constructivist Learning Model at MTs Nurul Huda Lembang, Bandung Barat - Ruslia; Mustajirin (EduSpirit : Jurnal Pendidikan Kolaboratif, 2025)
This Classroom Action Research (CAR) aims to improve students’ understanding of Fiqh at MTs Nurul Huda Lembang, Bandung Barat, by applying the Constructivist Learning Model. Fiqh, as a significant part of Islamic education, requires students to not only memorize but also deeply understand its concepts and principles, applying them in real-life situations. Traditional methods of teaching Fiqh often focus on rote learning, which limits students’ ability to connect the material with their daily lives. Therefore, this study explores how the Constructivist Learning Model, which emphasizes active learning, problem-solving, and critical thinking, can help students build their own understanding of Fiqh. The study was conducted in two cycles, involving 8th-grade students at MTs Nurul Huda Lembang. In each cycle, students were engaged in hands-on activities, group discussions, and problem-based learning tasks related to Fiqh topics, such as the rules of prayer, fasting, and zakat. The teacher facilitated learning by encouraging students to explore concepts, ask questions, and relate the content to their personal experiences. Data were collected through observations, student surveys, and pre- and post-tests to measure changes in student engagement and understanding. The results of the research indicated that the Constructivist Learning Model significantly improved students’ understanding of Fiqh. Students became more active participants in their learning, showed greater interest in discussing Islamic law, and demonstrated better critical thinking skills when applying Fiqh principles to real-life situations. This research suggests that the Constructivist Learning Model is an effective strategy for enhancing students’ comprehension of Fiqh and fostering a more interactive, student-centered learning environment.